Nutritional Interdependence Among Rumen Bacteria, Bacteroides amylophilus, Megasphaera elsdenii, and Ruminococcus albus - Miura, Hideki (1980)
Nutritional interdependence among three representatives of rumen bacteria, Bacteroides amylophilus, Megasphaera elsdenii, and Ruminococcus albus, was studied with a basal medium consisting of minerals, vitamins, cysteine hydrochloride, and NH(4)(+). B. amylophilus grew well in the basal medium supplemented with starch and produced branched-chain amino acids after growth ceased. When cocultured with B. amylophilus in the basal medium supplemented with starch and glucose, amino acid-dependent M. elsdenii produced an appreciable amount of branched-chain fatty acids, which are essential growth factors for cellulolytic R. albus. A small addition of starch (0.1 to 0.3%) to the basal medium containing glucose and cellobiose brought about successive growth of the three species in the order of B. amylophilus, M. elsdenii, and R. albus, and successive growth was substantiated by the formation of branched-chain amino acids and fatty acids in the culture. Supplementation with 0.5% starch, however, failed to support the growth of R. albus. On the basis of these results, the effects of supplementary starch or branched-chain fatty acids on cellulose digestion in the rumen was discussed.